Dimerised heterobifunctional reactive dyes. Part 1: characterisation using quadrupole time‐of‐flight mass spectrometry. (8th August 2018) - Sultana, Nadia; Liu, Yixin; Szymczyk, Malgorzata; Freeman, Harold S.; Vinueza, Nelson R.
Abstract : As part of an approach to enhancing the efficiency of reactive dye adsorption on cellulosic fibres at low electrolyte levels, commercially available dyes were dimerised using hexamethylenediamine (HMDA) as a linking group. A key component of this work involved using high‐resolution mass spectrometry (HRMS) to characterise a group of polysulphonated heterobifunctional monochlorotriazine/vinyl sulphone reactive dyes (CI Reactive Yellow 176, CI Reactive Red 239, CI Reactive Blue 221, CI Reactive Red 194 and CI Reactive Blue 222) and their dimeric analogs. In this respect, dimeric dye ions of differently charged states were observed using HRMS‐negative electrospray ionisation in combination with quadrupole time‐of‐flight mass spectrometry. For example, HRMS showed that the HMDA‐linked reaction products were mixtures of the target (unhydrolysed) dimers, hydrolysed dimers, monoreacted products and hydrolysed unreacted dyes, with CI Reactive Yellow 176 and CI Reactive Red 194 producing the desired unhydrolysed dimers.